2021
DOI: 10.1093/cercor/bhab072
|View full text |Cite
|
Sign up to set email alerts
|

Brain Basis of Psychopathy in Criminal Offenders and General Population

Abstract: Psychopathy is characterized by persistent antisocial behavior, impaired empathy, and egotistical traits. These traits vary also in normally functioning individuals. Here, we tested whether such antisocial personalities are associated with similar structural and neural alterations as those observed in criminal psychopathy. Subjects were 100 non-convicted well-functioning individuals, 19 violent male offenders, and 19 matched controls. Subjects underwent T1-weighted magnetic resonance imaging and viewed movie c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…Literatures have revealed that the anatomical basis of psychopathic traits might be more specifically associated with regions involved in emotional processing and integration of emotion into cognition, including the limbic and paralimbic regions ( 33 35 ), it supports the finding that high levels of psychopathic traits might be resulted from the dysfunction of the frontotemporal-limbic network ( 36 ). However, relevant studies examining the neural basis of psychopathic traits in violent patients with SZ are rare, especially on a brain morphological level.…”
Section: Introductionsupporting
confidence: 57%
“…Literatures have revealed that the anatomical basis of psychopathic traits might be more specifically associated with regions involved in emotional processing and integration of emotion into cognition, including the limbic and paralimbic regions ( 33 35 ), it supports the finding that high levels of psychopathic traits might be resulted from the dysfunction of the frontotemporal-limbic network ( 36 ). However, relevant studies examining the neural basis of psychopathic traits in violent patients with SZ are rare, especially on a brain morphological level.…”
Section: Introductionsupporting
confidence: 57%
“…In an earlier study with the same offender and control participants, the main findings were lower grey matter volumes in the anterior insula, frontal cortex, and the sensorimotor areas in the violent offenders compared to controls ( Nummenmaa et al, 2021 ). Following these earlier main findings, we found lower grey matter values in the bilateral insular cortex, left frontal pole, right precentral cortex, cingulate gyrus, left inferior temporal gyrus, and left fusiform cortex in the offender group compared to the control group.…”
Section: Discussionmentioning
confidence: 91%
“…We used voxel-base morphometry (VBM) to compare the regional grey matter volume between participants belonging to either of these study groups as well as a group of controls. In a recent structural brain imaging study using the same participants, the main findings were decreased grey matter volumes of the insula, the frontal cortex, and the sensorimotor cortex in violent offenders with psychopathic traits compared to control participants ( Nummenmaa et al, 2021 ). Based on prior studies, we predicted lower grey matter volume (GMV) values in temporo-parietal and cerebellar areas of the ASD compared to control participants.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…individuals who score high on both F1 and F2) v s those who do not ( Griffiths and Jalava, 2017 ; Hofhansel et al. , 2020 ) and report reductions in GMV in paralimbic structures (OFC, insula) ( Nummenmaa et al. , 2021 ), and the supplementary motor area ( Leutgeb et al.…”
Section: Neurobiology Of Interactive Effects Of Psychopathic Traitsmentioning
confidence: 99%